1998
DOI: 10.1111/0162-895x.00109
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity, Legitimizing Ideologies, and Social Status: A Matter of Ideological Asymmetry

Abstract: This paper examines the ideological asymmetry hypothesis with respect to the interface between legitimizing ideologies and psychological attachment to one's ethnic group. The ideological asymmetry hypothesis suggests that hierarchy-enhancing legitimizing ideologies should be positively associated with ingroup attachment among high-status groups, but that among low-status groups these associations should be either less positive in magnitude (isotropic asymmetry) relative to high-status groups or negative in dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
164
2
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(179 citation statements)
references
References 51 publications
10
164
2
3
Order By: Relevance
“…Consistent with this formulation, Levin et al (1998) reported that conservatism was associated with significant levels of ingroup favoritism among European and Asian American respondents and with significant levels of outgroup favoritism among Latinos and African Americans. Similarly, Jost and Thompson (2000, study 4) administered measures of political ideology and intergroup bias; conservatism was indeed associated with increased ingroup favoritism among European Americans (d = 0.30, n = 342) and increased outgroup favoritism among African Americans (d = -0.43, n = 105).…”
Section: Jost and Thompsonmentioning
confidence: 62%
See 1 more Smart Citation
“…Consistent with this formulation, Levin et al (1998) reported that conservatism was associated with significant levels of ingroup favoritism among European and Asian American respondents and with significant levels of outgroup favoritism among Latinos and African Americans. Similarly, Jost and Thompson (2000, study 4) administered measures of political ideology and intergroup bias; conservatism was indeed associated with increased ingroup favoritism among European Americans (d = 0.30, n = 342) and increased outgroup favoritism among African Americans (d = -0.43, n = 105).…”
Section: Jost and Thompsonmentioning
confidence: 62%
“…Although Hornsey, Spears, Cremers, and Hogg (2003) have found support for the maineffect hypothesis, several other studies have obtained the crossover interaction pattern and no main effect (see Jost, 2001;Jost & Burgess, 2000;Levin, Sidanius, Rabinowitz, & Federico, 1998;Major et al, 2002). A conceptually related hypothesis is that system justification tendencies in general should moderate the expression of ingroup and outgroup favoritism:…”
Section: Notedmentioning
confidence: 98%
“…Relationship between identification and deprivation 21 Verkuyten, 2003) would suggest that perceived discrimination and identification are negatively related: Levin, Sidanius, Rabinowitz and Federico (1998) found that identification and legitimising ideologies are negatively related for minority members;…”
Section: Discussionmentioning
confidence: 99%
“…For the former, it presents the possibility for maintaining their own culture and a greater likelihood of parity in terms of social equality. For the latter, cultural diversity and minority rights are often seen as threats to the dominant position and higher social status (e.g., Levin et al, 1998;Verkuyten & Thijs, 2002). This difference in attitude toward diversity can lead to problematic relational outcomes (Bourhis et al, 1997;Zagefka & Brown, 2002).…”
Section: Discussionmentioning
confidence: 99%